An Empirical Evaluation of a Modified Technology Acceptance Model for SAP ERP System. Issue 2 (3rd April 2022) - Hancerliogullari Koksalmis, Gulsah; Damar, Seckin
Abstract: SAP is the world leader in the enterprise resource planning (ERP) market with 25% market share. The objective of this study is to analyze and integrate several dynamics that have an impact on the adoption of SAP ERP system depending upon the modified technology acceptance model (TAM). Drawing from the TAM, four variables – actual usage, behavioral intention to use, perceived ease of use and perceived usefulness – are synthesized and integrated with panoptic empowerment, consultant support, learner-learner interaction, learner-teacher interaction, mastery goal orientation, personal innovativeness, satisfaction, top management support, trialability, and user guidance to develop a research model. Our sample is gathered through the end users that have experience on the SAP ERP system in an emerging country, Turkey. The structural equation modeling approach is able to be applied since our sample size (N = 584) is large enough. The SmartPLS is used to conduct the analyses which indicate that out of 23 hypotheses, 20 of them are supported. Moreover, this paper conducts a mediation effect analyses. The implications of the results are reviewed, and the recommendations are provided for further studies. This article links the theory and practice in SAP ERP systems by proposing a model, which offers novel perceptions for engineering managers who are in search of adopting the SAP ERP system.